A Comprehensive Review on Tunnel Field-Effect Transistor (TFET) Based Biosensors: Recent Advances and Future Prospects on Device Structure and Sensitivity - Reddy, N. Nagendra (Silicon, 2020)
In this fast-growing technological world biosensors become more substantial in human life and the extensive use of biosensors creates enormous research interest among researchers to define different approaches to detect biomolecules. The FET based biosensors have gained a lot of attention among all because of its high detection ability, low power, low cost, label-free detection of biomolecules, and CMOS compatible on-chip integration. The sensitivity of the biosensor inversely proportional to device size since they detect low concentration yields quick response time. Although FET based biosensor is having a lot of advantages among others but the short channel effects (SCE’s) and the theoretical limitation on the subthreshold swing (SS > 60mv/dec) of the FET leads to restrict device sensitivity and also have higher power dissipation due to the thermionic emission of electrons. To avoid these problems researchers focus shifts to the new technology FET based biosensors i.e. TFET based biosensors which are having low power and superior characteristics due to Band to band tunneling of carrier and steep subthreshold swing. This manuscript describes the full-fledged detail about the TFET based biosensors right from unfolding the device evaluation to biosensor application which includes qualitative and quantitative parameters analysis study like sensitivity parameters and different factors affecting the sensitivity by comparing different structures and the mechanisms involved. The manuscript also describes a brief review of different sensitivity parameters and improvement techniques. This manuscript will give researchers a brief idea for developing for the future generation TFET biosensors with better performance and ease of fabrication.